Protovoltaic boost DC/DC converter with adaptive perturb and observe-fuzzy maximum power point tracking algorithm - Mohd Zainuri, Muhammad Ammirrul Atiqi (2013)
Photovoltaic energy is one of the popular renewable energy sources. Its major issue is low efficiency of ultra-violet light to electrical energy conversion in about 30 % only. Irradiance and temperature are major factors to determine its ability to achieve maximum power output. Maximum power point tracking is developed in photovoltaic system to maintain maximum power output produced by its source. Boost dc-dc converter is used with maximum power point tracking algorithm to operate at desired voltage level. In the market, perturb and observe maximum power point tracking is the simplest and most popular but its main weaknesses are possibility of failing to track the maximum power point and inability to locate the point at low irradiance. In artificial intelligence approach, fuzzy logic control has quite significant drawback from its inputs. By using error and change of error as inputs which involve complicated mathematical process, it affects overall performance of maximum power point tracking. Therefore, this research work proposes design and development of photovoltaic boost dc-dc converter with adaptive perturb and observe-fuzzy maximum power point tracking algorithm, which is capable to extract energy at maximum operating level of photovoltaic module. This algorithm considers suitable parameters of various irradiance conditions especially at low irradiance and additional noise that occurs in the photovoltaic system, which contribute to originality of this research work. The simulation work covers modelling of photovoltaic module, boost dc-dc converter and maximum power point tracking algorithm to form a photovoltaic system. This system was evaluated under steady state and dynamic tests. For comparison purpose,conventional perturb and observe, and fuzzy logic control algorithms were modelled too. In hardware development, the prototype was developed and tested to verify simulation work. Multiple loads such as resistor, power light emitting diode and battery were used to test the prototype. From both simulation and experimental results, the proposed algorithm shows the best performance as compared to the conventional algorithms. It produces less overshoot (1 V), high maximum power ratio (98-100 %), fast time response, clean dc output, is tolerable with noise, and is more stable. Its significant achievement is through good performance at low irradiance. In conclusion, the proposed algorithm is able to extract maximum power of photovoltaic source effectively and dynamically, and is robust to various irradiation conditions.